Notch Signaling as a Regulator of the Tumor Immune Response: To Target or Not To Target? - Janghorban, Mahnaz; Xin, Li; Rosen, Jeffrey M.; Zhang, Xiang H.-F. (Frontiers in Immunology, 2018)
The Notch signaling pathway regulates important cellular processes involved in stem cell maintenance, proliferation, development, survival, and inflammation. These responses to Notch signaling involving both canonical and non-canonical pathways can be spatially and temporally variable and are highly cell-type dependent. Notch signaling can elicit opposite effects in regulating tumorigenicity (tumor-promoting versus tumor suppressing function) as well as controlling immune cell responses. In various cancer types, Notch signaling elicits a “cancer stem-cell (CSC)’ phenotype that results in decreased proliferation, but resistance to various therapies, hence potentially contributing to cell dormancy and relapse. CSCs can reshape their niche by releasing paracrine factors and inflammatory cytokines, and the niche in return can support their quiescence and resistance to therapies as well as the immune response. Moreover, Notch signaling is one of the key regulators of hematopoiesis, immune cell differentiation, and inflammation, and is implicated in various autoimmune diseases, carcinogenesis (leukemia), and tumor-induced immunosuppression. Notch can control the fate of various T cell types, including Th1, Th2, and the regulatory T cells (Treg), and myeloid cells including macrophages, dendritic cells and myeloid derived suppressor cells (MDSCs). Both MDSCs and Tregs play an important role in supporting tumor cells (and CSCs) and in evading the immune response. In this review we will discuss how Notch signaling regulates multiple aspects of the tumor promoting environment by elucidating its role in CSCs, hematopoiesis, normal immune cell differentiation, and subsequently in tumor-supporting immunogenicity.